A Label-Free and Ultrasensitive Prussian Blue-Based Dipstick Sensor for Bacterial and Biofilm Detection - Vincy, Antony (Langmuir : the ACS journal of surfaces and colloids, 2023)
Water and food contamination has become the major contributor to infections and deaths. However, rapid and sensitive bacterial detection still remains an unmet demand that has attracted widespread attention. Often water and food samples are sent out for laboratory testing to detect the presence of contamination, which is time-consuming and laborious. Herein, we have developed a highly sensitive, tenable, affordable, and robust (STAR) paper-based colorimetric dipstick sensor based on the principle of Prussian blue (PB) synthesis as an indicator of bacterial contamination. In the presence of bacteria, it leads to the formation of PB, a dye that acts as a colorimetric indicator. The intensity of the PB is the direct measure of the degree of contamination. The fabrication of the STAR dipstick sensor involves a simple and cost-effective process. The STAR dipstick sensor is ultrasensitive and can detect up to 101 CFU/mL of bacteria within minutes of contact with the test sample. The STAR dipstick sensor is fabricated using biodegradable components, which is speculated to facilitate quick and environmentally friendly degradation after each use. The sensor has been validated for its properties and capabilities at different pH to detect both Gram-positive and Gram-negative bacterial strains in real-time samples. The stability and degradation were also monitored. Comprehensively, the proposed STAR dipstick sensor can serve as a point-of-care device to detect bacterial contamination in a swift and sensitive manner